Augmenting combat power: Military translation in China-Burma-India Theater - Luo, Tian (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2016)
Despite the growing academic interest in translators and interpreters in war, there is still a need to discuss the nature and role of translation from the perspective of military principles. This paper, drawing upon the theories about combat power, defines military translation as an intangible factor of combat power involving information and knowledge, and proposes a framework to map out how translation acts upon the internal mechanism of war. Based on the relevant historical records about and memoirs by the interpreters serving in the China-Burma-India Theater, the case study was able to discover that interpreters contributed greatly to the victory of the Alliance through their bilingual services that increased tangible and other intangible factors of combat power, and aided in its execution. This paper concludes that military translation can help reshape the combat power relations between the parties involved in conflicts, and ultimately influence the outcome of the war.